Lumine. Vol. 2 - Krogell, Emma (WEBTOON UNSCROLLED, 2024)
"Before Lumine met Kody, he was a down-on-his-luck weredog with nowhere to turn. Now that Lumine has a job as Kody's bodyguard and a place to live, his life should be simpler. But things are only growing more complicated. Kody is still doing everything to keep Lumine at arms length, mysteries are piling up, and witch kids are going missing. Lumine tries to protect the antisocial Kody from his bullies, but can't figure out why popular witch girl Calla is doing everything in her power to make him miserable. And there are more questions surrounding the brooding teenager-how come his magic doesn't work properly? And why is there a cat-shaped spirit haunting him? Plus, Lumine has his own mystery to solve. He is a werewolf, a rare and powerful type of magical being thought to be extinct, but he can't transform properly. Lumine is stuck in either his human form or as a tiny puppy dog, and has no idea why. When danger closes in on Kody, Lumine does everything to protect him, even at the risk of revealing his big, fluffy secret. To keep each other safe, the unlikely duo will have to unlock the mysteries of their powers . . . and figure out how to get along."--Amazon.com.